Inskriptionen på Øster Hornum fonten - Rump, Erling (Kirkehistoriske Samlinger, 1972)
The Inscription on the Font in Oester Hornum. In Western Himmerland, Jutland, the Oester Hornum church is situated. Its baptismal font has a remarkable majuscule inscription on the rim of the font. The inscription is almost illegibly carved (fig. 2.), and has therefore not been fully deciphered and explained during later research. Because of the superficial carving the letters must be presumed to have been painted. The author has deciphered the text and published it in 1958 (footnote 1). In its entirety the text says: * QVONIACD APVD TE EST FONS VITE • ET IN LVMINE TVO • VIDEBICD LVCD * Near the • there is a hole in the stone shaped like a holder of a candle, which also is quite in accordance with the symbolism after »and in your light«. As further it has been a practice ever since the primitive Church after every Roman-Catholic christening ceremony to light a candle for the newly baptized, the picture fits very well. The text comes from the Vulgate: psalm XXXV, 10: »For with thee is the fountain of life, and in thy light we shall see light«, -[39]. The first verse is clear around a baptismal water. The second verse is just as symbolically clear when one thinks of the wax candle being mirrored in the water. Searching further I found that the majuscule inscription existed as versiculus after »Rex sanctorum angelorum« yet as »Domine apud te est fons vite« etc. - Rex sanctorum is a hymn which was sung ad descensum fontis at the Easter vigil in the early MiddleAges. Later it has been left out of Missales Romanum. In the article the rather lengthy mediaeval baptismal ritual is shortly gone through. Benedictio fontis is described thoroughly in order to show that the baptismal water in the font during the consecration, which traditionally took place on Easter eve, was divided 10 times by the priest ad modum crusis: by the hand, by blowing, and by pouring crisma or oil or wine into the font. This corresponds to the geometrical construction of our font inscription (fig. 3.). According to the first prophesy (Genesis, chapt. 1, 1-31, chapt. 2, 1-2) the cross is oriented after the points of the compass with the light from the East, from where the Second Coming can be expected. The sinking of the Easter candle (Lumini Christi) three times into the baptismal water, which has a strong sexual touch, the pouring of the fertilizing crisma, wine, and oil during benedictio fontis as well as the exorcisms are referred and described under foot-note 25. Reference is made to C.G.Jung’s treatment of benedictio fontis in »Psychologie und Religion« (Rascher Verlag, Zürich) and to D.R. Dendy »The Use of Lights in Christian Worship«, especially chapt. 8, Lights in Baptism. An old mediaeval relief on the Bjäresjö font in Scania (old Danish area) is mentioned in the article. It represents the baptism of Jesus in a cup-shaped font (fig. 4). St. John the Baptist gives a candle to Jesus according to the usual ritual practice. At the end a short epigraphic treatment of the inscription is given. The stroke formed majuscules are being compared with the corresponding ones on the Bayeux tapestry and is suggested to date back to about year 1100. [39] The former translation. - The new one: Salm: 36, 9: »For with thee is the fountain of life, and in thy light we are bathed with light«. -